2016
DOI: 10.5897/ajps2016.1401
|View full text |Cite
|
Sign up to set email alerts
|

Growth responses of two varieties of Heliconia flowers to selected growth media in Port Harcourt, South-South Nigeria

Abstract: Lack of suitable variety as well as appropriate growth medium constitutes major problems to flower production. It is against this backdrop that a pot experiment was carried out in the Department of Crop and Soil Science Demonstration Plot, Faculty of Agriculture, University of Port Harcourt, Nigeria between April and May, 2013 to determine the growth responses of two varieties of Heliconia flowers to selected growth media. The experiment comprised of two Heliconia varieties (Jade and Golden Torch) and six (6) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Similarly maximum leaf area (2.62 cm 2 ) was noticed in Sahil hybrid which was statistically at par with Salar hybrid having leaf area (2.59 cm 2 ), while minimum leaf area (2.32 cm 2 ) and (2.31 cm 2 ) were found in Sandal and Anna, respectively (Fıgure 1). Leaf area of the plant depends upon the availability of the nutrients as reported by [23]. Their results revealed that high leaf area in top soil + peat moss (1:1) media might be due to the ability of the plant to retain nutrients and water for translocation to shoot system.…”
Section: Single Leaf Area (Cm 2 )mentioning
confidence: 79%
“…Similarly maximum leaf area (2.62 cm 2 ) was noticed in Sahil hybrid which was statistically at par with Salar hybrid having leaf area (2.59 cm 2 ), while minimum leaf area (2.32 cm 2 ) and (2.31 cm 2 ) were found in Sandal and Anna, respectively (Fıgure 1). Leaf area of the plant depends upon the availability of the nutrients as reported by [23]. Their results revealed that high leaf area in top soil + peat moss (1:1) media might be due to the ability of the plant to retain nutrients and water for translocation to shoot system.…”
Section: Single Leaf Area (Cm 2 )mentioning
confidence: 79%
“…Heliconia (Golden torch) is one of the beautiful and popular cut flowers in Nigeria. Many species of the plant are found in the tropics (Albuquerque et al, 2014, Omovbude et al, 2016. In addition to their exotic beauty, they also have a natural postharvest vase life of 6-8 days after which senescence occurs resulting in rapid wilting of the petals.…”
Section: Introductionmentioning
confidence: 99%
“…Top soil is commonly used as a growing medium. Rojas et al [5] report that the emergence across the five plant species was higher in the topsoil growth media compared to the other soil materials, most likely due to its larger available water content as a consequence of increased amounts of organic C. Top soils are generally unsatisfactory for the production of plants in containers because the soils do not provide the aeration, drainage, and water holding capacity required for plant growth [6].…”
Section: Introductionmentioning
confidence: 99%
“…Sand provides excellent support and gas exchange but has insufficient water and nutrient supplying capacity. Since water is held on the surfaces of particles, sand has a small water reserve [6].…”
Section: Introductionmentioning
confidence: 99%